Welfare Comparisons: Sequential Procedures for Heterogeneous Population - Peter Lambert; Xavi Ramos (Center for Economic Studies and ifo Institute (CESifo), 2001)
Some analysts use sequential dominance criteria, and others use equivalence scales in combination with non-sequential dominance tests, to make welfare comparisons of joint distributions of income and needs. In this paper we present a new sequential procedure which copes with situations in which sequential dominance fails. We also demonstrate that the recommendations deriving from the sequential approach are valid for distributions of equivalent income whatever equivalence scale the analyst might adopt. Thus the paper marries together the sequential and equivalizing approaches, seen as alternatives in much previous literature. All results are specified in forms which allow for demographic differences in the populations being compared.
Keywords: 330